Embedding Supply Chain Agility in Relationship between Energy Management Practices and Renewable Energy Supply Chain: An Empirical Investigation - Sudawan Somjai; Pornkul Suksod; Natnaporn Aeknarajindawat (International Journal of Supply Chain Management, 2019)
In present economy, energy management practices is one the important source for reducing the energy consumptions in industrial sector and creating sustainability in organizations by producing renewable energy supply chain. The purpose of the current study is to investigate the relationship among energy management practices such as management commitment, energy awareness, energy knowledge, energy audit with renewable energy supply chain. It further investigates the supply chain agility as mediator. The nature of the current study is descriptive and quantitative. The data for present study is collected from manufacturing companies in Thailand by using self-administered questionnaire. 300 questionnaires are distributed in manufacturing companies by using simple random sampling technique. The smart PLS has been used for data analysis. The finding of the study shows that all the hypotheses are accepted and shows the positive and significant results. The findings reveal that the energy management practices such as management commitment, energy awareness, energy knowledge, energy audit have significant influence on renewable energy supply chain and supply chain agility significantly mediates the relationship. Further discussion and limitation of the study is also discussed at the end of the study.